Sex difference in skeletal muscle mass in relation to metabolic dysfunction-associated steatotic liver disease: a propensity score matching study - Da-Hye Son; Yu-Jin Kwon; Jun-Hyuk Lee (Elsevier, 2024)
Background: While low muscle mass is considered a risk factor for metabolic dysfunction-associated steatotic liver disease (MASLD), whether the relationship is independent of fat mass remains unclear. Objectives: This study aims to clarify the association between the sex-specific height-adjusted low skeletal muscle mass index (LSMI) and MASLD. Methods: Data from the 2008-2010 Korean National Health and Nutrition Examination Survey were analyzed. LSMI was defined using the 2019 Asian Working Group for Sarcopenia. The non-alcoholic fatty liver disease-liver fat score was used to assess MASLD. Gender-specific 1:1 propensity score matching (PSM) was performed to mitigate the confounding effects of anthropometric variables and lifestyles. Conditional logistic analysis was used on the dataset after PSM to estimate the odds ratio (OR) with a 95% confidence interval (CI). Results: After PSM, the prevalence of MASLD was significantly higher in men with LSMI than in those without LSMI (37.4% vs. 29.6%). No significant difference was observed in the prevalence of MASLD between groups after PSM in women (20.4% vs. 20.3%). Conditional logistic analysis revealed that the odds of having MASLD were significantly higher in men with LSMI compared to those without LSMI (OR = 1.38, 95% CI: 1.09-1.75), while no significant association was found in women with LSMI (OR = 1.10, 95% CI: 0.87-1.40). Conclusion: Height-adjusted LSMI is an independent factor associated with MASLD in the condition of the same level of fat mass in men. Further prospective studies in diverse populations are needed to confirm our findings.